Neighborhood‐level index of knowledge and intellectual capital. Issue 1 (2015) - Bedford, Denise A. D.; Kelley, Sean; Bible, Geoffrey; Kollinger, Justin; Savage, Kelsey; Brown, Gabrielle; Sabatiuk, Liz
ABSTRACT: This poster presents a rationale and architecture for a neighborhood‐ and city‐level index of knowledge and intellectual capital. The Index is grounded on established models of intellectual capital and knowledge transactions. The architecture includes seven components that support analytics and engagement. The analytics component includes data harvesting, harmonization, management, dashboards and reports. The engagement component is grounded on GIS components and is designed to enable a city's citizens to leverage the Index to achieve their vision of a Knowledge City. Six facets of a Knowledge City are defined, and factors that contribute to the incentivizing or Disincentivizing of knowledge transactions are proposed. The model and methodology are currently being implemented in four cities – Columbus and Youngstown Ohio, Baltimore Maryland, and Fredericksburg Virginia.